2019
DOI: 10.3389/fmicb.2019.01174
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Profiles of Serum Exosomes Derived From Individuals With Latent and Active Tuberculosis

Abstract: Tuberculosis (TB) has been the leading lethal infectious disease worldwide since 2014, and about one third of the world’s population has a latent TB infection (LTBI). This is largely attributed to the difficulties in diagnosis and treatment of TB and LTBI patients. Exosomes offer a new perspective on investigation of the process of TB infection. In this study, we performed small RNA sequencing to explore small RNA profiles of serum exosomes derived from LTBI and TB patients and healthy controls (HC). Our resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 54 publications
1
83
0
1
Order By: Relevance
“…TB was about 90% according to a meta-analysis of newly reported evidence from 20 studies [27]. Furthermore, we and other groups have illustrated that there were M.tuberculosis nucleic acids in exosomes derived from plasma of both patients and healthy specimens as well as M.tuberculosis non-infected macrophages in vitro [28][29][30]. Considering the DNA extraction method we used here, the detected sequences in plasma may include bacterium genome DNA, circulating DNA as well as exosomal DNA.…”
Section: Discussionmentioning
confidence: 86%
“…TB was about 90% according to a meta-analysis of newly reported evidence from 20 studies [27]. Furthermore, we and other groups have illustrated that there were M.tuberculosis nucleic acids in exosomes derived from plasma of both patients and healthy specimens as well as M.tuberculosis non-infected macrophages in vitro [28][29][30]. Considering the DNA extraction method we used here, the detected sequences in plasma may include bacterium genome DNA, circulating DNA as well as exosomal DNA.…”
Section: Discussionmentioning
confidence: 86%
“…In this cohort, expression levels of miRNAs was similar in subjects co-infected with HIV and in those without HIV infection [ 86 ]. A recent study in China, which analyzed miRNA expression profile by RNA-sequencing in serum exosomes, found overexpression of miR-1246, miR-2110, miR-370-3p, miR-28-3p, miR-193b-5p and downregulation of miR-3675-5p in active TB, but also identified a set of miRNAs exclusively expressed in latent TB [ 85 ]. No validation experiments in a second cohort of patients were performed.…”
Section: Biomarker Discovery Studiesmentioning
confidence: 99%
“…miRNA has also been used to differentiate LTBI from active TB. By studying 250 miRNAs, Lyu et al (2019) also identified the patterns where the hsa-let-7e-5p, hsa-let-7d-5p, hsa-miR-450a-5p, and has-miR-140-5p were differentially expressed among patients with LTBI; whilst hsa-miR-1246, hsa-miR-2110, hsa-miR-370-3p, hsa-miR-28-3p, hsa-miR-193b-5p were associated differentially expressed among patients with active TB.…”
Section: Prospects Of Biomarkers By Unbiased "Omics" Approachmentioning
confidence: 99%